The awareness of Gharar in online shopping among Taman Bukit Mewah’s resident / Siti Munirah Yacob. - Yacob, Siti Munirah (2019)
This research is conducted for the academic paper project with the title, “The Awareness of Gharar in Online Shopping Among Taman Bukit Mewah’s Resident”. Nowadays, as we know, online shopping is common among shoppers. Generally, online shopping is a form of electronic commerce, which allows consumers to directly buy goods or services from a seller over the Internet using a web browser. As advanced technology, shopping activities are also more convenient due to technological development. But as existence of online shopping, it has raised doubts in Muslim society because of uncertainty (gharar) like the buyer cannot see the exact condition of goods. Muslims scholars gives a lot of opinions regarding this according to Al-Quran, Sunnah, Ijma’. Many Muslims especially faced problems because of gharar element that exist in the transactions. This study wants to overlooked the awareness of gharar among society and the target are Taman Bukit Mewah’s Resident. Thus, the objectives of this research are, 1) to study the awareness of gharar in online shopping among the respondents 2) to identify the effects of gharar in online shopping to the respondents. 3) to determine the best solutions and suggestion to minimize gharar in online shopping. The researcher uses quantitative method and collected data through online survey. To achieved the three objectives, the survey was spread diligently through WhatsApp and collected 68 responses. It is found that majority of the respondents do aware about gharar in online shopping, but actually many party like seller and authorization aside from consumer, also play roles in minimising gharar element together in online shopping industry.